Assessment of Pulp Vitality Using Pulse Oxymetry Versus Electric Pulp Testing in Traumatized Teeth - Fatima Habib, Hafiz Muhammad Tufail,Syed Muhammad Hussain Zaidi, Fahad Salim KhanHammal Khan Naseer Baloch, Sadaf Raffi, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A randomized clinical trial evaluated diagnostic accuracy of pulse oximetry (PO) versus electricpulp testing (EPT) in 80 traumatized permanent incisors. Participants were randomized to testingat 1 week, 1 month, and 3 months post-trauma. Primary outcomes included pulp vitality status